If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3p + -2) + -1(p + 4) = 3p Reorder the terms: 2(-2 + 3p) + -1(p + 4) = 3p (-2 * 2 + 3p * 2) + -1(p + 4) = 3p (-4 + 6p) + -1(p + 4) = 3p Reorder the terms: -4 + 6p + -1(4 + p) = 3p -4 + 6p + (4 * -1 + p * -1) = 3p -4 + 6p + (-4 + -1p) = 3p Reorder the terms: -4 + -4 + 6p + -1p = 3p Combine like terms: -4 + -4 = -8 -8 + 6p + -1p = 3p Combine like terms: 6p + -1p = 5p -8 + 5p = 3p Solving -8 + 5p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. -8 + 5p + -3p = 3p + -3p Combine like terms: 5p + -3p = 2p -8 + 2p = 3p + -3p Combine like terms: 3p + -3p = 0 -8 + 2p = 0 Add '8' to each side of the equation. -8 + 8 + 2p = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 2p = 0 + 8 2p = 0 + 8 Combine like terms: 0 + 8 = 8 2p = 8 Divide each side by '2'. p = 4 Simplifying p = 4
| -1+-5h=14 | | 4.4x=-36.52 | | 9b^2=-15b+14 | | 18-2(5x+4y)= | | 2x^2+14x-12=0 | | -2g+7=3 | | 4x-x+3=x+15 | | 5x^3-2x^2-25x+10= | | 2x^2-11x-11=0 | | -3c-4=8 | | x^2+20x+47= | | -8(X-2)-5(3-X)+16=15-4(3-X) | | 4x-6-x=12 | | 7x+1=71 | | -2e-6=10 | | -7f=21 | | 5a+4=3a+2 | | 7y-2=7y-y | | 8x+4+130+3x-6=180 | | 36=4(9-5) | | 6x+6=-54 | | 3(2a+5)=5(3a-6) | | -4+5h=2+3h | | 10h+125=7h+230 | | 3k+-2=10 | | 7h+125=7h+230 | | .03x+.1(200-x)=.05(200) | | 3(b-5)=-2b | | 4(k-3)=-6(-2k+2) | | 7Z+10-4z=1+2z+7 | | .5(x+3)=2.5 | | 7x-9=68 |